THE INFLUENCE OF PROBLEM-BASED LEARNING ON ACADEMIC PERFORMANCE OF HIGHER LEARNING INSTITUTION STUDENTS - Sarah Sabir Ahmad; Azfahanee Zakaria; Mhd Azmin Mat Seman (International Journal of Accounting, Finance and Business, 2023)
Problem-based learning (PBL) has been widely discussed as a teaching approach to enhance learning by pushing students to work together in groups to resolve real-world problems while strengthening their subject-matter expertise, critical thinking skills, and interpersonal skill. Recognizing this, the goal of this study is to examine the impact of problem-based learning (PBL) on academic performance among students at higher learning institution. This study discusses the factors of PBL which consist interpersonal competence, analytical skill, learning assessment, and interdisciplinary learning and how it significantly affect students' academic success. In order to determine this, a sample of 116 students were selected as the respondents for this study and the data was gathered using self-administered questionnaires. Using SPSS statistical software, the results were examined and the findings showed three variables of PBL has significant effects on the students’ academic performance. Therefore, the governing body should take action to integrate PBL in classroom learning activities since it will improve students' comprehension, encourage improved communication skills, increase student involvement, and hold their interest for a longer period of time than traditional teaching and learning techniques.